Carriage rates and antimicrobial resistance of Staphylococcus aureus and methicillin-resistant Staphylococcus aureus in Ethiopia: A systematic review and meta-analysis - Mengistie Yirsaw Gobezie; Minimize Hassen; Tewodros Solomon; Mulat Belete Demessie; Getahun Worku; Husien Nurahmed Toleha; Nuhamin Alemayehu Tesfaye (PLoS ONE, 2025)
Background Staphylococcus aureus (S. aureus) and methicillin-resistant S. aureus (MRSA) are significant public health concerns globally due to their high prevalence and increasing antimicrobial resistance. This study aimed to assess the carriage rate of S. aureus and its antimicrobial resistance profile in Ethiopia. Methods A comprehensive literature search was conducted in electronic databases, including PubMed, Google Scholar, Hinari, SCOPUS, and EMBASE, for articles published between 2013 and 2024. From 159 potential studies, 19 observational studies reporting S. aureus carriage rates and/or antimicrobial susceptibility in Ethiopia were included in the final analysis. The Joanna Briggs Institute (JBI) critical appraisal checklist was used to assess the quality of the studies. The data synthesis and reporting were conducted in accordance with the PRISMA checklist guidelines. A random-effects meta-analysis was performed to pool the estimates. Heterogeneity was assessed using Q statistics, I2 statistics, meta-regression, and sensitivity analysis. Publication bias was evaluated subjectively with a funnel plot and Egger’s regression test, with p < 0.05 indicating the presence of publication bias. Results The pooled carriage rate of S. aureus was 25% (95% CI: 21–29%). The pooled odds ratio between MRSA and MSSA was 0.31 (95% CI: 0.21–0.46). Subgroup analysis showed the highest carriage rates before 2019, in the Oromia and SNNPR regions and HIV-positive patients. Egger’s regression test (p < 0.001) and trim and fill analysis adjusted the pooled carriage rate to 17.4% (95% CI: 12.6–22.2). Sensitivity analysis confirmed the robustness of the findings. High resistance rates were observed for penicillin (93%), ampicillin (80%), and amoxicillin (67%), with vancomycin (3%), ceftriaxone (5%), and clindamycin (6%) showing the lowest resistance rates. Conclusion This systematic review and meta-analysis revealed a substantial carriage rate of S. aureus in Ethiopia, with nearly one-third of the isolates being MRSA. Significant regional and demographic variations were observed. These results underscore significant regional variations, highlighting the need for targeted interventions. High resistance rates to common antibiotics were found, emphasizing the need for enhanced infection control and judicious antimicrobial use in Ethiopia.